BUDIDAYA DAN PRODUKSI KOPI DI SULAWESI BAGIAN SELATAN PADA ABAD KE-19 - Ashabul Kahpi (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2017)
Coffee has been known as a commodity by the inhabitants of southern Sulawesi since the 17th century, but its commercial cultivation was only done by the encouragement Dutch colonial government in the upland areas in the directly ruled Governments lands (bergregentschappen) since 1860. Coffee was cultivated in the upland Northern Districts, Bantaeng in the Southern Districts, Bulukumba and Sinjai in Eastern Districts, Selayar Island where coffee was cultivated by the inhabitants in cooperation with the governments officials and village-heads. The cultivated cofffe was exported overseas to countries such as The Netherlands, Singapore, United States, France, Papua Nuginea, Dili Timor, and areas around the Dutch Indies